Clinical Development of Molecular Targeted Therapy in Head and Neck Squamous Cell Carcinoma. Issue 4 (12th November 2019) - Gougis, Paul; Moreau Bachelard, Camille; Kamal, Maud; Gan, Hui K; Borcoman, Edith; Torossian, Nouritza; Bièche, Ivan; Le Tourneau, Christophe
Abstract: A better understanding of cancer biology has led to the development of molecular targeted therapy, which has dramatically improved the outcome of some cancer patients, especially when a biomarker of efficacy has been used for patients' selection. In head and neck oncology, cetuximab that targets epidermal growth factor receptor is the only targeted therapy that demonstrated a survival benefit, both in the recurrent and in the locally advanced settings, yet without prior patients' selection. We herein review the clinical development of targeted therapy in head and neck squamous cell carcinoma in light of the molecular landscape and give insights in on how innovative clinical trial designs may speed up biomarker discovery and deployment of new molecular targeted therapies. Given the recent approval of immune checkpoint inhibitors targeting programmed cell death-1 in head and neck squamous cell carcinoma, it remains to be determined how targeted therapy will be incorporated into a global drug development strategy that will inevitably incorporate immunotherapy.